Perdagangan Internasional dan Pertumbuhan Ekonomi Negara Berkembang: Systematic Literature Review - Rissa Kharisma; Siti Nuri Azizah; Niza Mufnah Ultia; Lisa Ayu Maharani (Jurnal Ekonomi dan Bisnis Digital, 2026)
International trade plays an important role in supporting economic growth, especially in developing countries. The main issue discussed in this study is the extent to which international trade influences economic growth and the factors that determine its effectiveness in developing countries. This study aims to analyze the relationship between international trade and economic growth through a Systematic Literature Review (SLR) approach. The method used is a literature review by identifying, evaluating, and analyzing previous research articles related to international trade and economic growth in developing countries. The results show that international trade generally has a positive impact on economic growth through increasing exports, expanding market access, encouraging investment, and supporting technological development. However, the benefits of international trade depend on economic policies, competitiveness, and the readiness of each country in managing global economic activities.